Evaluating the aesthetic and amenity performance of vegetated stormwater management systems - Buffington, Jared (Kansas State University, 2012)
Stormwater management within the urban context has evolved over time. This evolution has been categorized by five paradigm shifts (Novotny, Ahern, & Brown, 2010). The current paradigm of stormwater management utilizes hard conveyance and treatment infrastructure designed mainly to provide protection for people from typical 1-5 year frequency storms. Consequently, this infrastructure is sometimes unable to deal with larger sized, 50 to 100 year events which can have serious consequences. Manhattan, Kansas has suffered multiple flooding episodes of severe proportion in the past decade. The dilemma of flooding within the Wildcat Creek watershed is a direct example of the current paradigm of stormwater management. This once ecologically healthy corridor is fed by conveyance systems that do not address the hydrologic needs of the watershed; decreasing the possibility for infiltration and groundwater recharge. Vegetated stormwater management systems must be implemented to help increase infiltration and address flooding problems within the Wildcat Creek watershed. The aesthetic performance of designed landscapes has a tremendous effect on the appreciation and care given to them by the surrounding population (Gobster, Nassauer, Daniel, and Fry, 2007). Landscape architecture has the ability to aid in the visual appeal and ecological design of vegetated stormwater management systems (SMS) by utilizing existing frameworks that address aesthetic reaction of the outdoor environment (Kaplan, Kaplan, and Ryan, 1998). This document evaluates design alternatives of vegetated SMS in order to discern a set of variables that inform the relationship between each systems aesthetic and amenity performance and their ecosystem and hydrological performance. Identified variables are combined into a set of guidelines for achieving different levels, or patterns of aesthetic performance found within the Understanding and Exploration Framework et al. (Kaplan, Kaplan, and Ryan, 1998) and amenity performance listed by Echols and Pennypacker’s Amenity Goals et al. (2007) through vegetated SMS. These design guidelines illustrate how aesthetic theory can be applied through ecological systems in order to increase the coherence, legibility, complexity, and mystery (Kaplan & Kaplan, 1989) of existing sites. Creating spaces where ecological and socio-cultural activities can coexist addresses the local characteristics of aesthetics with the universal dilemma of stormwater management.
Keywords: Stormwater management; Aesthetic amenity; Aesthetic performance; Aesthetics (0650); Landscape Architecture (0390); Water Resource Management (0595)